(untitled) (Research, Society and Development, 2020)
Currently, there is a serious pandemic caused by COVID-19, which has an incisive impact on the entire social scene, including the religious sphere. Umbanda is a Brazilian religion, based on syncretism that involves African, indigenous and Catholic influences. In the face of this circumstance, the aims of the study are to identify the structure of the representations of COVID-19 among Umbanda’s practitioners in the Rio de Janeiro (city) and to analyze the contents of the representations of COVID-19 among the people mentioned before, through the Structural Approach of the Social Representations Theory. It is a descriptive research, with a qualitative approach and carried out in a virtual environment with the participation of 100 Umbanda’s practitioners in the Rio de Janeiro (city), mostly women, with an average age over 40 years, who present or live with someone who has a chronic disease and who have had or know people, whose COVID-19 exam’s results were positive. The results indicate that the structure of the representations of COVID-19 among the participants is composed of central and peripheral elements, that link and complement each other, giving meanings to their experiences in relation to the instituted reality, interfering with their practices, attitudes and behaviors. It is concluded that the representations of COVID-19 among Umbanda’s practitioners configure the expression of conscious thought and in accordance with scientific principles and guidelines, withdrawing from any magical character and expectations of solutions that emerge exclusively from the sacred and the sitiuatios that transcends.